The frontier of simulation-based inference - Cranmer, Kyle; Brehmer, Johann; Louppe, Gilles (Proceedings of the National Academy of Sciences - PNAS, 2020)
Many domains of science have developed complex simulations to describe phenomena of interest. While these simulations provide high-fidelity models, they are poorly suited for inference and lead to challenging inverse problems. We review the rapidly developing field of simulation-based inference and identify the forces giving additional momentum to the field. Finally, we describe how the frontier is expanding so that a broad audience can appreciate the profound influence these developments may have on science.